2004
DOI: 10.4028/www.scientific.net/kem.269.199
|View full text |Cite
|
Sign up to set email alerts
|

Development of Forsterite with High Q and Zero Temperature Coefficient τ<sub>f</sub> for Millimeterwave Dielectric Ceramics

Abstract: High-Q pure forsterite (Mg 2 SiO 4 ) ceramics with Qf = 240,000 GHz were developed by the usual solid sintering process, using raw materials of highly purified MgO and SiO 2 .The τ f (temperature coefficient of the resonant frequency) was a large and negative: -60 to -70 ppm/ºC. To adjust the τ f value to zero, rutile (TiO 2 ) with high τ f (450 ppm/ºC) was added. When sintering temperature was selected as low as possible, TiO 2 remained in the forsterite specimen, which raised τf from a negative to positive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 2 publications
0
23
1
Order By: Relevance
“…Some ceramics of the silicate series, which have the low constant, are considered to be the appropriate candidates for the commercial applications at the high frequency because of the high Q · f and the low ε r values. For example, the forsterite, i.e., Mg 2 SiO 4 , is known to have the Q · f value of 102/ [332] Makio Nishizuka et al 210000 GHz and the dielectric constant of approximately 6 [1]. Moreover, the compensation of τ f value to be achieved 0 ppm/ • C and the low temperature co-fired ceramic (LTCC) of the Mg 2 SiO 4 ceramic were also reported in the literature [2][3][4].…”
Section: Introductionmentioning
confidence: 87%
“…Some ceramics of the silicate series, which have the low constant, are considered to be the appropriate candidates for the commercial applications at the high frequency because of the high Q · f and the low ε r values. For example, the forsterite, i.e., Mg 2 SiO 4 , is known to have the Q · f value of 102/ [332] Makio Nishizuka et al 210000 GHz and the dielectric constant of approximately 6 [1]. Moreover, the compensation of τ f value to be achieved 0 ppm/ • C and the low temperature co-fired ceramic (LTCC) of the Mg 2 SiO 4 ceramic were also reported in the literature [2][3][4].…”
Section: Introductionmentioning
confidence: 87%
“…For example, Tsunooka et al [3] mentioned that forsterite (Mg 2 SiO 4 ) possesses a low e r of 6.8 and a high Q Â f of 242,000 GHz. Zhang et al [4] reported that the CaMgSi 2 O 6 ceramic sintered at 1300 8C has a relatively lowpermittivity (7.46) and high Q Â f value (59,700 GHz).…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, a number of dielectric ceramics with low K and high Qf values have been investigated, such as Al 2 O 3 [1], MgAl 2 O 4 [2], ZnAl 2 O 4 [3], and Mg 2 SiO 4 [4]. In particular, Zn 2 SiO 4 ceramic systems have been widely studied due to their high Qf values.…”
Section: Introductionmentioning
confidence: 99%